EKSISTENSI SENI PERTUNJUKAN LUAMBEK DALAM KEHIDUPAN MASYARAKAT NAGARI KEPALA HILALANG KECAMATAN 2 X 11 KAYU TANAM KABUPATEN PADANG PARIAMAN - Zahara Kamal (Universitas Andalas, 2012)
Luambek is a performance art tradition which is an integral part of socio-cultural life of Nagari Kepala Hilalang. For the people, this social ceremony enlivened by Luambek called Alek Pauleh, which create a social force in the nagari and reflect direct relationship within social structure. The existence of Luambek is related to the ownership of art itself. Furthermore, Luambek is positioned as